Pembinaan Moral dan Spiritual pada Warga Binaan (Studi Kasus di Lembaga Pemasyarakatan Kelas IIA Pekanbaru) - try wiganda irfan; hasrul hasrul; Isnarmi Isnarmi (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2019)
This study discusses the process of moral and spiritual formation of prisoners in the Pekanbaru Class IIA Correctional Institution. The purpose of the study was to find out and analyze the form of implementation of moral and spiritual formation in Pekanbaru Class IIA Correctional Institution. This research uses descriptive method with a qualitative approach. The technique of collecting data is through interviews, documentation and observations of officials, prison officials, dai and pastors and assisted citizens. The results of the study showed that the forms of moral and spiritual formation in the assisted citizens of the Class IIA Correctional Institution in Pekanbaru were in the form of oral preaching